2018
DOI: 10.3889/oamjms.2018.223
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Cardiopulmonary Resuscitation Services in Sub-Saharan Africa: A Survey of Suggestions Made by Health Care Workers in Cross River State, Nigeria

Abstract: BACKGROUND:Rising trend in Non-Communicable Diseases (NCDs) in developing countries often result in sudden death, which are largely preventable through effective cardiopulmonary resuscitation (CPR). Most communities in Sub-Saharan Africa, however, lack access to CPR services, due to a deficiency in requirements for the establishment of such services. These requirements can be grouped into a triad of awareness, infrastructure and capacity building.AIM:This study was aimed at assessing the perceived need and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 26 In Nigeria and South Africa, studies found that most participants felt trainings should be provided in order to improve resuscitation, especially for teachers in the school setting. 27 29 The South Africa study also identified major barriers to bystander CPR, including fear of being sued if something goes wrong, presence of secretions, fear of injury to the victim, fear of contracting a disease from the victim and belief that someone else would do it. Furthermore, participants were more likely to provide CPR for immediate family or children rather than adult strangers.…”
Section: Resultsmentioning
confidence: 99%
“… 26 In Nigeria and South Africa, studies found that most participants felt trainings should be provided in order to improve resuscitation, especially for teachers in the school setting. 27 29 The South Africa study also identified major barriers to bystander CPR, including fear of being sued if something goes wrong, presence of secretions, fear of injury to the victim, fear of contracting a disease from the victim and belief that someone else would do it. Furthermore, participants were more likely to provide CPR for immediate family or children rather than adult strangers.…”
Section: Resultsmentioning
confidence: 99%
“…Lower rates of CPR training is more common in some countries, as a study in Greece identified that only 6.5% of the general population in a county region had received training in the last 12 months (Konstandinos et al , 2008 ). In a study conducted in sub-Saharan Africa, the majority of the communities not only had limited awareness of CPR but also lacked the capacity and infrastructure to encourage, deliver or facilitate CPR education (Kalu et al , 2018 ). Kalu and colleagues (2018) noted that both healthcare professionals and the general public needed training in CPR, noting the importance of the bystanders involvement leading to improved outcomes (Kalu et al , 2018 ).…”
Section: Background and Significancementioning
confidence: 99%
“…In a study conducted in sub-Saharan Africa, the majority of the communities not only had limited awareness of CPR but also lacked the capacity and infrastructure to encourage, deliver or facilitate CPR education (Kalu et al , 2018 ). Kalu and colleagues (2018) noted that both healthcare professionals and the general public needed training in CPR, noting the importance of the bystanders involvement leading to improved outcomes (Kalu et al , 2018 ). A study conducted in Ghana noted that 90% of 479 survey respondents had never undertaken CPR training, and 25.4% of the 190 ambulance workers surveyed had also not completed any training in relation to resuscitation (Anto-Ocrah et al , 2020 ).…”
Section: Background and Significancementioning
confidence: 99%
“…The presence of a skilled healthcare provider should be an added advantage to the victim. The triad of insuffi cient awareness, infrastructure and capacity building however, continue to pose a challenge to the performance of optimum cardiopulmonary resuscitation (CPR) even among healthcare workers [2].…”
Section: Introductionmentioning
confidence: 99%